2016
DOI: 10.17159/2310-3833/2016/v46n1a10
|View full text |Cite
|
Sign up to set email alerts
|

Opinions of occupational therapists on the positioning of vocational rehabilitation services in Gauteng Public Healthcare

Abstract: Introduction: A collaborative effort to transform occupational therapist's vocational rehabilitation services in Gauteng

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…The hope is that eventually the tool can be used in vocational rehabilitation services to help therapists do quality management and provide information for planning and policy making. Tool dissemination could also raise an awareness of the scope of vocational rehabilitation services that occupational therapists can offer as so many practices are doing only the assessment aspect of vocational rehabilitation 48 .…”
Section: Discussionmentioning
confidence: 99%
“…The hope is that eventually the tool can be used in vocational rehabilitation services to help therapists do quality management and provide information for planning and policy making. Tool dissemination could also raise an awareness of the scope of vocational rehabilitation services that occupational therapists can offer as so many practices are doing only the assessment aspect of vocational rehabilitation 48 .…”
Section: Discussionmentioning
confidence: 99%
“…A literature search of South African studies yielded initiatives related to more informal types of employment, including self-employment, and finding or starting stipendiary occupation as an alternative to seeking paid employment 18,28 . Facilitating self-employment was not considered as part of their professional competencies by experts in vocational rehabilitation training for occupational therapists in South Africa, as suggested by Buys in 2015 18 .…”
Section: Literature Reviewmentioning
confidence: 99%
“…The importance of accurate and skilled reporting of functional capacity evaluations are highlighted in several articles which also uses the ethical element of report writing 1,3,[8][9][10][11][12][13][14] . Escorpizo et al 15 indicated that a successful vocational rehabilitation programme relies on the interrelationship between several elements and they note that effective communication between the employer and the healthcare practitioner is one such element.…”
Section: Literature Reviewmentioning
confidence: 99%